COVID-19, domestic violence and abuse, and urgent dental and oral and maxillofacial surgery care (2020)
Household isolation measures to reduce coronavirus transmission during the COVID-19 pandemic have resulted in increased risk of domestic violence and abuse (DVA). DVA physical injury most frequently involves the face. Dentists, dental care professionals, oral surgeons and oral and maxillofacial surgeons all have a critical part to play in identifying patients experiencing DVA, who present with dental and facial injury, and in making referrals to specialist agencies. This paper describes how to ask questions about DVA sensitively and how to make an appropriate referral. Early intervention and referral to a DVA advocate can prevent an abusive situation becoming worse with more intense violence. It can save lives.